Stereotypes and self-perception of the elderly in the peruvian national television, 2016 - Alarcón Llontop, Luis Rolando (2016)
In the absence of thorough studies that cross national television and older adults (PAM, by its acronym in Spanish), their self-perception and stereotypes in fiction programs on Peruvian television were analyzed. From the naturalistic paradigm, qualitative methodology and use of classical and phenomenological hermeneutics, observation techniques (with record cards per se) and focus groups (with guiding questions) were applied on two populations: 1) fiction programs, and 2) PAM in Chiclayo, Piura and Trujillo. It was concluded that several PAM stereotypes are handled in national fiction TV. In that regard, the PAM interviewed have mixed feelings and they would like to be reflected honorable, capable of overcoming conflicts, twinned with each other, enjoying their family, and able to be happy.